نموذج نظري في إعداد وحدة دراسية نموذجية لأغراض مهنية في وظيفة إعلانية لغير الناطقين باللغة العربية = A theoretical model in preparing a model Linguistic unit for professional purposes in an advertising job for non-Arabic speakers - Ali, Asem Shehadeh Saleh (IIUM, 2022)
ملخص البحث الإعلان أو الدعاية أو الإشهار (بالإنجليزية : Advertising وبالفرنسية : Publicité ، وهو أحد الأنشطة الإعلامية التي لا غنى عنها للأنشطة الاقتصادية من صناعة وتجارة وخدمات وغيرها من الأنشطة الاقتصادية، وكذلك بالنسبة للمؤسسات والمنظمات الخيرية وغير الربحية والتي دون الإعلان عن مجهوداتها فلن تحصل على الدعم المجتمعي والتمويل المادي اللازم لاستمرارها في عملها وأدائها لرسالتها. وليست صناعة الإعلانات من الفنون المستحدثة، وإنما هي قديمة قدم التاريخ، فقد بدأ الإعلان على أشكال تطورت بمرور القرون حتى أصبح فن الإعلان كما نعرفه الان؛ ولذلك الوضع، فإن هذا البحث يحاول إجابة تلك الأسئلة والمشاكل والصعوبات بإعداد وحدة دراسية نموذجية مناسبة للموظفين أو الطلبة المتخصصين في قسم تعليم اللغة العربية لأغراض خاصة الذين لهم رغبة كبيرة في مشاركة هذا المجال. يسعى هذا البحث إلى الكشف عن كيفية الحصول على معلومات الإعلانات، وبيان حاجات اللغة العربية المطلوبة في مجال الإعلاني، وبيان معايير كتابة الإعلانات الجيدة، ويتبع المنهج الوصفي؛ وذلك باستقصاء نموذج من الدروس والوحدات الدراسية في قضية تعليم اللغة العربية لأغراض خاصة. الكلمات المفتاحية: الأغراض الخاصة، الإعلانات، مفهوم المنهج، نموذج نظري Abstract Advertising, publicity, or publicity (in English: Advertising and in French: Publicité, which is one of the media activities that are indispensable for economic activities such as industry, trade, services, and other economic activities, as well as for charitable and non-profit organizations and organizations that without announcing their efforts will not receive community support and funding. The material needed to continue its work and fulfill its mission. The advertising industry is not a new art, but rather it is as old as history, advertising began in forms that developed over the centuries until it became the art of advertising as we know it now, and for this situation, this research attempts to answer those questions, problems and difficulties by preparing A model unit suitable for employees or students specialized in the Department of Teaching Arabic for Special Purposes who have a great desire to participate in this field. This research seeks to reveal how to obtain advertising information, indicate the needs of the Arabic language required in the field of advertising, and indicate the criteria for writing good advertisements. The descriptive approach is followed by investigating a model of lessons and units of study in the issue of teaching Arabic for different purposes especially.